THE EFFECT OF E-SERVICE QUALITY ON REPURCHASE INTENTION WITH TRUST AND CUSTOMER SATISFACTION AS MEDIATING VARIABLES: A SYSTEMATIC LITERATURE REVIEW - Cici Anggraini; Budi Eko Soetjipto; Madziatul Churiyah (RADJA PUBLIKA, 2026)
The rapid growth of digital commerce has intensified competition among e-commerce platforms, making repurchase intention an essential indicator of long-term customer retention. Although E-Service Quality (ESQ) has been widely recognized as a major determinant of online consumer behavior, prior research remains fragmented regarding the mechanisms through which ESQ influences repurchase intention, particularly through trust and customer satisfaction. This study addresses that gap by systematically synthesizing prior empirical evidence on the relationships among these constructs in e-commerce settings. This Systematic Literature Review (SLR) follows the PRISMA framework to ensure methodological rigor and transparency. The search process identified 3,122 articles, of which 53 studies met the inclusion criteria and were retained for the final synthesis. The findings indicate that E-Service Quality consistently leads to repurchase intention, though this effect generally operates indirectly through trust and customer satisfaction as mediating mechanisms. Prior studies further suggest a sequential process in which higher E-Service Quality strengthens consumer trust, increases satisfaction, and ultimately encourages repeat purchasing behavior. This review consolidates previously scattered findings to offer a more integrated conceptual framework of the ESQ–repurchase intention relationship. It identifies important directions for future research in digital consumer behavior studies.